Neutralizing effects of anti-infliximab antibodies on synergistically-stimulated human coronary artery endothelial cells. (December 2019) - Ogrič, Manca; Poljšak, Katjuša Mrak; Lakota, Katja; Žigon, Polona; Praprotnik, Sonja; Semrl, Snezna Sodin; Čučnik, Saša
Abstract: Background and aims: Patients with rheumatic diseases have an increased risk of atherosclerosis with up-regulated serum amyloid A (SAA), tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), which were reported to activate human coronary artery endothelial cells (HCAEC). We aimed to investigate the effects of TNF-α inhibitor infliximab and anti-infliximab antibodies on the TNF-α/IL-1β/SAA activated HCAEC. Methods: HCAEC were incubated with TNF-α, IL-1β, SAA, infliximab, anti-infliximab antibodies and their combinations. The protein levels of pro- and anti-atherogenic analytes were measured in supernatants using ELISA and multiplex assays, while mRNA expression was determined by RT-PCR. Anti-infliximab antibodies were purified from sera samples by affinity chromatography. Results: IL-6, IL-8, GM-CSF and GRO-α were synergistically up-regulated in triple stimulation with TNF-α, IL-1β and SAA, while their levels in solely SAA- or TNF-α-stimulated HCAEC did not increase. IL-1Ra, IL-1α, VCAM-1, MCP-1, IL-10 and IL-17A were increased, but no synergistic responses were observed in triple stimulation. Infliximab was effective in lowering the synergistic effect of IL-6, IL-8, GM-CSF and GRO-α in triple stimulation, while anti-infliximab antibodies restored the levels. The changes were confirmed at the mRNA expression level for IL-6, IL-8 and GM-CSF. Conclusions: Triple stimulation with TNF-α, IL-1β and SAA synergistically elevated IL-6, IL-8, GM-CSF and GRO-α release in supernatants of HCAEC, with infliximab substantially inhibiting their levels. An isolated, enriched fraction of polyclonal anti-infliximab antibodies was capable of neutralizing infliximab, in the presence of TNF-α/IL-1β/SAA. The long-term presence of anti-infliximab antibodies in the circulation of patients with chronic rheumatic diseases is potentially important for promoting the atherosclerotic process. Graphical abstract: Image 1 Highlights: TNF-α, IL-1β and SAA synergistically elevated IL-6, IL-8, GM-CSF and GRO-α release in HCAEC supernatants. Infliximab was effective in lowering synergistically elevated IL-6, IL-8, GM-CSF and GRO-α release. IL-1Ra, IL-1α, VCAM-1, MCP-1, IL-10 and IL-17A were increased, but no synergistic responses were observed. An isolated fraction of polyclonal anti-infliximab antibodies was capable of neutralizing infliximab. Anti-infliximab antibodies in the circulation are potentially important for promoting atherosclerosis in patients.